The Design and Implementation of the Massively Parallel Processor Based on the Matrix Architecture. - Noda, H. (IEEE Journal of solid state circuits)
This paper describes the design and implementation of the massively parallel processor based on the matrix architecture which is suitable for portable multimedia applications. The proposed architecture in this paper achieves the high performance of 40 GOPS in the case of consecutive fixed-point 16-bit additions at 200MHz clock frequency and the small power dissipation of 250mW. In addition, 1Mbit SRAM for data registers and 2048 2-bit-grained processing elements connected by a flexible switching network are integrated in the small area of 3.1 mm 2 in 90nm CMOS low standby technology. These design techniques and architectures described in this paper are attractive for realizing area-efficient, energy-efficient, and high-performance multimedia processors